E-010 Tips and Tricks in using Onyx in Preoperative Embolization of Hypervascular Intracranial Tumors. (26th July 2014) - Reddy, S; Thomas, A; Fusco, M; DiNobile, D; Ogilvy, C
Abstract : Onyx embolization is a well-established preoperative treatment of cerebrovascular arterio venous malformations and fistulae. We report four cases of hypervascular extraaxial tumor embolization using Onyx administration as an adjunct to traditional particle embolization and coils. We report three cases of meningioma and one case of hemangiopericytoma. These tumors are highly vascular tumor arising from the meninges, the core of the tumor predominantly supplied by the middle meningeal artery and the periphery supplied by parasatization by intracerebral branches. Hypervascular extraaxial tumor resection may cause very high volume blood loss during open surgery. Presurgical embolization of these lesions has been proven to significantly decrease intraopertaive blood loss and facilitate subsequent surgical resection. Various agents has been used in the past for embolization of these tumors including polyvinyl alcohol (PVA), gelfoam powder, gelatin microspheres, liquid adhesives and coils. For the last few decades until recently, PVA particle embolization has been the mainstay of embolization and has been widely used. Onyx is a nonpolymerizing liquid agent composed of ethylene-vinyl alcohol copolymer dissolved in dimethyl sufloxide. When injected, Onyx precipitates within vessels forming a spongy cast. We report the use of Onyx in the embolization of four cases of hypervascular extraaxial tumors. The average was 57 yrs of age and 2 males and 2 females. Technique included a guide catheter placement in the external carotid artery and a microcatheter in the distal branch of the middle meningeal artery. The guide catheter we used was a 6F Neuron catheter and the microcatheters used included marathon microcatheter and more recently a DUO catheter. A 0.38 DAC was also used in one of the cases. Advantages of Onyx embolization include a more controlled injection due to gradual precipitation in a centripetal fashion which allows for slower and more accurate injections as well as penetration of very small calibre vessels. It also has the advantages of penetrating into the branches supplied by other vascular territories. Special caution is recommended to make sure the onyx doesn't reflux into the intracerebral arteries supplying the periphery of the tumor. In the first case we did not use the particles. During embolization using Onyx, there was occlusion of the catheter with onyx at the catheter tip and Onyx wouldn't go forward and was only refluxing back and we had to abort the procedure. Although the major vessel supplying the tumor was thrombosed the tumor core itself was not embolised. In all the later cases we embolised initially with particles and then went on to complete the embolization with Onyx. This report furthers the growing body of literature confirming the safety and efficacy of Onyx in the preoperative embolization of Intracranial highly vascular extra axial tumors. Disclosures: S. Reddy: None. A. Thomas: None. M. Fusco: None. D. DiNobile: None. C. Ogilvy: None.